FACTORS SHAPING CAPITAL STRUCTURE: EVIDENCE FROM PRIVATE COMMERCIAL BANKS IN BANGLADESH - Shahriar, A. H. M.; Alam, Mohammad Jahangir; Biswas, Al Amin; Rumaly, Nishat; Golder, Uttam (International Journal of Accounting & Finance Review, 2021)
This study investigates how various determinants shape the capital structure of commercial banks in Bangladesh, employing panel data, structured from available secondary sources, covering 22 banks as samples from 61 scheduled banks for the period of 2011 to 2020, conducting Feasible Generalized Least Squared (FGLS) Regression Model. Several diagnostic tests have been conducted to ensure the robustness and stability of the model. The study results reveal that return on assets, earnings per share, asset growth, asset structure, investment structure, cost per loan assets, and loan loss provisioning considerably influence the capital structure or the leverage of commercial banks. On the contrary, the authors find no explicit evidence that bank size, liquidity, capital adequacy, and non-performing loan ratio have significant impacts on the capital structure of the banking industry of Bangladesh. The findings of this study advocate that return on assets, earnings per share, asset structure, and cost per loan assets as the dominant explanatory factors of capital structure. Besides, asset growth, investment structure, and loan loss provisioning affect less significantly on determining the capital structure of the banking industry. This study also brings the academicians, researchers, and analysts with corroborating new routes for exploring further research in this field. JEL Classification Codes: G21, G32, O16.